Muslim World : islam breaks fresh ground - "Rastogi, Tara Charan" (Delhi, 1986)
In this book the author Ecologises Islam and studies It. In relation To non-violence, arts And sciences, secularism, Marxism-Leninism; Its philosophy, political system, Morality, Ilfluence on Hinduism etc.